Diseño y desarrollo de estrategias para la Fundación Zoológica de Cali 2011-2013 (2011)
The proposed objective is to develop a methodology that allows a NGO, of unique character, the Zoo Foundation located in the city of Cali – Colombia . 3 ; the design of organizational strategies for the period between 2011 – 2013 replicable in any zoo park. Tools are being used to develop a vision, mission and values with system thinking; strategic thinking is promoted by getting to know the different schools of strategy and applying them to the activity of the NGO. Balanced Score Card is also applied, finishing with the statement of objectives and task; by applying them, the guidelines for conservation proposed by WAZA, World Association of Zoos and Aquariums 4